PENDEKATAN SISTEM DALAM MENGKAJI DAKWAH ISLAM - Uus Uswatusolihah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2007)
This article focussed on Islamic preaching (da’wa) studied through system approach. This system is a way of thinking about job managing. It provides a framework for describing internal and external environmental factors that influence each other as a whole. The author concluded that the system of da ’wa constituted an entity that comprised of many elements of da’wa. They involved input, output, mind and behavioral convertions, and social and cultural environment. Then, the succes of da’wa is determined by the qualities of input, the level of difficulties mad’u faced, and the sincerity of da’i and his capability to manage the input into good output. So, the use of system approach in da’wa studies gives another perspective to solve the more of recent da’wa problems.